Enzyme-responsive polymeric micelles with fluorescence fabricated through aggregation-induced copolymer self-assembly for anticancer drug delivery. Issue 48 (20th November 2020) - Yan, Ke; Zhang, Shujing; Zhang, Kun; Miao, Yalei; Qiu, Yudian; Zhang, Panke; Jia, Xu; Zhao, Xubo
Abstract : The TPE moiety with AIE is employed as functional hydrophobic chain to induce copolymer self-assembly and form polymeric micelle that can show enzyme-responsive drug delivery. Abstract : Designing polymer-based nanostructures through self-assembly has great practical significance in biomedical applications, especially in drug delivery. In general, hydrophobic chains can induce the self-assembly of amphiphilic copolymer to form polymer-based nanostructures in an aqueous phase. However, the application of polymer-based nanostructures has been prevented due to the insufficient functionality of hydrophobic chains. To address these critical issues, the unique tetraphenylethene (TPE) moiety is employed with aggregation-induced emission (AIE) as functional hydrophobic chains to induce copolymer self-assembly and form polymeric micelles that can show strong fluorescence and a low critical micelle concentration (CMC) in aqueous solution. The novel polymeric micelles can efficiently encapsulate doxorubicin (DOX) molecules, and their favorable stability is demonstrated in a physiological medium. More importantly, the disassembly of polymeric micelles is triggered in the presence of esterase, then causing drug release and fluorescence quenching. It is demonstrated that DOX-loaded polymeric micelles have an obvious toxicity against cancer cells. This work confirms that the combination of AIE and self-assembly is an effective strategy for expanding the application of block copolymers and developing new enzyme-responsive polymeric micelles for cancer therapy.